Occupational health and safety in the general services sector on two campuses of a public university located in Juazeiro do Norte-CE and Crato-CE: a case study - Januário, Thays Lorranny da Silva; Marinho, Jefferson Luiz Alves (Brazilian Journal of Production Engineering, 2020)
Introduction: In Brazil, there are almost two million workers who perform the cleaning and conservation activity, constituting one of the most prominent economic segments in the country’s economy. Given this, it is of fundamental importance to study all the risks that general service professionals are subjected to in order to look for ways to prevent, combat and correct problems arising from various threats. Objective: This article aimed to propose improvements to optimize the Health and Safety at Work (WSH) conditions of cleaning and conservation workers based on current legislation and scientific literature. Methods: This article is classified as a case study, exploratory and qualitative approach, on two URCA campuses. Were utilized: literature review and direct observation were used for job analysis. Results: Many shortcomings were found by the contractor, which is where the greatest responsibility lies with the employees, and too of contractor. Conclusion: All problems checked can be fixed. It is proposed to comply with current legislation applied to the category (Law No. 13.429, of March 31, 2017) and the Regulatory Standards on the part of contracted and the contractor.